(untitled) (OODBODHAN, 2025)
The Antilock Braking System (ABS) is a crucial safety feature in modern vehicles which prevents wheel lock-up during braking and maintains steerability. The non-linear behavior of different road conditions makes it difficult to predict the optimal brake forces to be applied to minimize the stopping distance and maintain steerability. Control techniques play a crucial role in the optimization of the performance of ABS. This study explores various control strategies, including Bang-Bang, Proportional – Integral – Derivative (PID), and Fuzzy Logic controllers, to enhance the effectiveness of ABS by developing a mathematical and MATLAB/Simulink model of the components. The parameters to be controlled are optimal slip and brake pedal force based on the input parameters which are slip, road condition, coefficient of friction and wheel acceleration. Results indicate that the Fuzzy controlled ABS causes the vehicle stop after about 12.9 sec which is 24.11 % faster than vehicle without ABS and 7.8% faster than vehicle with Bang-Bang controller. The PID controlled ABS causes the vehicle stop after about 12.7 sec which is 25.29 % faster than vehicle without ABS and 9.2% faster than vehicle with Bang-Bang controller and 1.5 % faster than Fuzzy controller. While Bang-Bang control offers simplicity, it lacks precision and efficiency compared to PID and Fuzzy Logic approaches. However, the PID controller demonstrates superior performance, striking a balance between stability and responsiveness. Overall, the PID and Fuzzy controllers exhibit notable advancements in ABS control, ensuring safer braking and enhanced vehicle steerability.